Pengembangan Eco-Mind Media Based on Cybernetic Theory for Developing Understanding of a Harmonious Ecosystem in Elementary School Science and Social Studies Learning - Pande Komang Primandani; Gede Agung Anak AGung; Ayu Dewi Sutyaningsih Anak AGung (Jurnal Media dan Teknologi Pendidikan, 2026)
Learning the ecosystem topic still faces obstacles in the form of low conceptual understanding, limited availability of interactive IPAS learning media particularly for ecosystem materials and suboptimal student engagement. This study aims to: (1) describe the design and development of the Eco-Mind media, (2) determine the feasibility of the Eco-Mind media based on expert judgments and trial results, and (3) examine the effectiveness of the Eco-Mind media in improving students’ learning outcomes. The media was developed using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The feasibility test results showed percentages of 88.67% from the design and development expert, 84.61% from the subject matter expert, 93.33% from the instructional design expert, 93.75% from the learning media expert, 91.6% in the individual trial, and 96% in the small group trial, all of which fall into the good to very good qualification categories. The effectiveness test results indicated that the calculated t-value (15.47) was greater than the t-table value (2.04) at the 5% significance level, indicating that the Eco-Mind media is feasible and effective for use in IPAS learning on harmonious ecosystem topics. This study contributes to improving the quality of IPAS learning on ecosystem materials and provides evidence that learning media can be integrated with cybernetic theory. This media also offers a solution to the problem of limited learning resources.